ENHANCEMENT OF DISSOLUTION CHARACTERISTICS OF CLOPIDOGREL BISULPHATE BY PRONIOSOMES - MAZYED, EMAN A.; ZAKARIA, SHERIN (International Journal of Applied Pharmaceutics, 2019)
Objective: The present investigation aims to formulate and evaluate proniosomes of clopidogrel bisulphate for improving its dissolution characteristics. Methods: The slurry method was used for the preparation of proniosomes of clopidogrel using cholesterol, sorbitan monostearate (Span 60) and maltodextrin as a carrier. Clopidogrel proniosomes were evaluated for their entrapment efficiency and in vitro drug release. The best formula (F1) that achieved maximum drug release was further evaluated by measurement of the angle of repose, morphological examination, determination of vesicle size, determination of zeta potential, Fourier transform infrared spectroscopy and differential thermal analysis. The in vivo behavior of the selected proniosomal formula (F1) was studied by measuring the antiplatelet activity in adult male mice. Results: The entrapment efficiency of clopidogrel proniosomes was in the range of 83.04±1.99 to 90.14±0.30. % drug released from proniosomal formulations was in the range of 79.73±0.35 to 97.70±1.10 % within 4 h. Clopidogrel proniosomes significantly enhanced the in vitro release of clopidogrel compared with the plain drug that achieved 61.77±2.22 % drug release. F1 significantly (p ≤ 0.001) increased the bleeding time and bleeding volume and significantly (p ≤ 0.05) prolonged prothrombin time and decreased prothrombin activity and increased the international normalized ratio (INR) compared to plain clopidogrel. Conclusion: The present investigation introduced proniosomes as a promising carrier for clopidogrel that could enhance its dissolution and pharmacological effect.